Il Trimble Express fa tappa a Roma - Redazione, Redazione (GEOmedia, 2008)
Trimble Express stops over Rome Trimble Express is a european road show set up to promote the latest news regarding Trimble technologies. The event stopped in Italy, in 5 different cities.On May 29th the stopover was in Rome at Borgo di Tragliata. The event was organized by Crisel, a Trimble instruments dealer in Lazio and Umbria.